The Influence of PLI Experience and Soft Skills on Work Readiness with Work Motivation as a Mediator among Students of Akademi Pariwisata Bunda Padang - Yulia Mandasari; Ida Rochanawati; Musparni Musparni; Naseh Ulwan; Akrimullah Mubai (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study examines the influence of Industrial Field Practice (PLI) Experience and Soft Skills on Work Readiness among students of Akademi Pariwisata Bunda Padang, with Work Motivation as a mediating variable within the Stimulus-Organism-Response (SOR) theoretical framework. Using a quantitative approach with total sampling, data were collected from all 40 students of the 2024 cohort and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS, incorporating bootstrapping procedures and outer model evaluation. Results indicate that PLI Experience directly and significantly influences Work Readiness (β = 0.839; T = 8.792), but does not significantly affect Work Motivation (T = 0.727; p = 0.467). Soft Skills emerged as the most dominant predictor of Work Motivation (β = 0.921; T = 25.340; p < 0.001) and significantly predicted Work Readiness directly (β = 0.589; T = 4.098). Work Motivation significantly mediates only the Soft Skills–Work Readiness pathway (indirect effect = 0.381; T = 2.800; p = 0.005). These findings confirm the SOR Framework's applicability in vocational tourism education and highlight the strategic need for institutions to strengthen PLI quality and embed structured soft skills development within the curriculum to produce competitive hospitality graduates.